ASSOCIATIVE MEANING AND COMMUNICATIVE EFFECT (MEANING DELIVERY) - Juli Rachmadani Hasibuan (BAHAS, 2016)
Associative meaning is an unstable meaning that has variants based on individual experience. The associative meaning of an expression has to do with individual mental understanding of the speaker. They can be broken up into five subtypes are connotative meaning, stylistic meaning, affective meaning, reflected meaning, and collocative meaning. The semantic analysis, generally, must explain how the sentences of a particular language are understood, interpreted, and related to states, processes and objects in the world. When learns more about semantics, it finds out a lot about how the world's languages match forms to meanings. And in doing that, learns a lot about ourselves and how we think, as well as acquiring knowledge that is useful in many different fields and applications. Keywords : semantics, associative meaning, communicative effect